Effect on hasty state for driver's visual perception - Miyaji, Masahiro (2012 IEEE International Conference on Vehicular Electronics and Safety, 2012)
Driver's hasty state is one of major psychosomatic states which may result in traffic accidents. This paper describes an effect on hasty state as to driver's perception by means of detecting the change of driver's useful view of field and time to perception of a moving object. Hasty state was reproduced by means of using a scenario of traffic incidents in rush operation on a driving simulator basis. A stereo camera based tracking unit was used for measurement of movement of driver's eyes and head while driving ahead in traffic incidents occurring situation. It was clarified that driver's useful field of view had decreasing tendency, meanwhile time to percept to the moving object was prolonged when subjects operated rush driving to a destination. Finally we propose a concept to provide information on psychosomatic states to a driver was in order to lower a potential risk to be involved in a traffic accident.